2013
DOI: 10.1016/j.otsr.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Relevancy and reproducibility of magnetic resonance imaging (MRI) interpretation in multiple-ligament injuries and dislocations of the knee

Abstract: Level IV, prospective case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Similar results were found by Halinen et al [ 11 ], and Kosy et al [ 12 ]. In terms of reproducibility, Barbier et al [ 13 ] demonstrated that MRI lacks precision and reproducibility, and the diagnosis should be integrated with clinical exam and stress X-rays. It has been also reported that MRI was inferior to clinical examination [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Halinen et al [ 11 ], and Kosy et al [ 12 ]. In terms of reproducibility, Barbier et al [ 13 ] demonstrated that MRI lacks precision and reproducibility, and the diagnosis should be integrated with clinical exam and stress X-rays. It has been also reported that MRI was inferior to clinical examination [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the first studies that analyzed MRI accuracy in dislocated knees found very good sensitivity and specificity for most of the studied structures, 5,16,23,26,30 with a PPV greater than 90% for all the major ligaments (ACL, PCL, PLC, MCL, and patellar tendon), 26 those findings were not replicated in subsequent studies. 1,3,10 The small sample size of these initial studies, 5,16,23,26,30 together with incomplete comprehension of the anatomy of the knee at the time, could explain their overestimation of the diagnostic accuracy of MRI to identify MLKIs. Some of these studies did not include all types of MLKIs, 5,30 recorded incomplete data, 26 and lacked statistical power 23,26,30 to reach firm conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The American Journal of Sports Medicine 2023;51(2):429-436 DOI: 10.1177/03635465221145697 Ó 2023 The Author(s) examination is usually difficult to make because of pain and swelling, 3,10,16 stress radiography 1,9,13 and MRI are essential to establish an accurate diagnosis. 1,10,27 MRI is considered the gold standard for the diagnosis of ligament, meniscal, and chondral lesions of the knee, 7 but not many studies have investigated the accuracy of MRI in identifying injury patterns in MLKIs. y Initial studies found good accuracy of MRI in assessing MLKIs.…”
Section: Because a Clinical Diagnosis Based On Anmentioning
confidence: 99%
“…Second, this study did not assess the inter-observer reliability for assessing MRI findings and this might increase the accuracy of MRI because inter-observer agreement for MRI findings for soft tissue disruption has been reported to be low. 36 Finally, this study included acute (<4 weeks after injury) and chronic (>4 weeks after injury) injuries, which may not reflect the true accuracy of the MRI. 30…”
Section: Discussionmentioning
confidence: 99%